Imaging Findings of Cyst Hydatid Lesions in a Patient with Multiorgan Involvement: A Case of Hydatid Cyst with Multiorgan Involvement - Bozdag, Pinar Gundogan; Bozdag, Ahmet; Boyuk, Abdullah (Galenos Yayincilik, 2020)
Hydatid disease (HD) is a zoonosis caused by the larval form of the Echinococcus granulosus parasites in which human is the intermediate host. Hydatid cysts mainly develop in the liver and lungs. However, they can be found in all anatomical locations, especially in endemic areas. Herein, we present a case of HD involving the liver, kidney and breast with the findings of mammography, ultrasonography and computed tomography.
Multiorgan tutulumu olan hastada kist hidatik lezyonlarının görüntüleme bulguları multiorgan tutulumu olan kist hidatik olgusu
Keywords: Hydatid cyst; multiorgan; breast; renal